Consumer Decision-Making in E-Commerce: How Brand Image, Advertising Appeals, and Reviews Influence the Purchase of Dhozen Apparel on Shopee - Noerdiana, Muhammad Ichsan Multazam; Herlina, Listri; Muttaqin, Ridlwan (International Journal of Marketing & Human Resource Research, 2025)
This study addresses the issue of declining sales of Dhozen products on Shopee, which is concerning amid the growing trend of online fashion shopping. This research aims to analyze the influence of brand image, advertising appeal, and consumer reviews on the purchase decisions of Dhozen products. The data were through a survey of university students in Bandung.The regression analysis results show that the three variables have a significant influence on purchase decisions. However, partially, the consumer reviews variable does not have a considerable impact, Due to brand image and advertising appeal being particularly strong for Dhozen products, consumers might prioritize these factors over review, This study concludes that strengthening brand image and managing advertising appeal are crucial strategies for Dhozen to enhance its competitiveness in the market. Furthermore, this research contributes to the digital marketing literature by providing insights into effective marketing strategies for local brands on e-commerce platforms.